PENGELOLA KEUANGAN DAERAH YANG BERWENANG MELAKUKAN PERGESERAN ANGGARAN DALAM KEADAAN DARURAT - Nina Anggreni; Rusdianto Sesung (Fakultas Hukum Universitas Narotama, 2023)
Local governments are required to always improve their adaptability, as an organization they must be able to make decisions, manage risks, encourage change and solve problems in their regions. Considering that budgeting adaptation is carried out with a fast response time, shifting the budget as an initial alternative can then be accommodated in budget changes. In order for local governments to maintain the principles of good governance, it is necessary to pay attention to the limits of authority that must be exercised by regional financial managers so that the implementation of budget shifts meets the criteria and complies with statutory provisions. This study aims to provide academic descriptions and recommendations for local governments in setting budget shift policies in emergencies. This study discusses the limits of authority and legal conformity for regional financial managers to shift budgets in emergencies. The conclusion of this study is that the regional financial manager's authority to shift the budget in an emergency is permissible, but full of limitations both on procedures or procedures, as well as limitations on authority. Meanwhile, legal conformity can be carried out in accordance with the provisions of Government Regulation Number 12 of 2019 concerning Regional Financial Management and Minister of Home Affairs Regulation Number 77 of 2020 concerning Technical Guidelines for Regional Financial Management. In order to perfect the implementation of the budget shift policy, a Regional Head Regulation concerning Procedures for Budget Shifts must be formed.Keywords: financial manager, budget shift, emergency.